Design of a Load Balancing Control System for Efficient Power Distribution in Yavatmal City - Shriya P. Kundankar; Sakshi D. Burkhande; Sakshi P. Gore; Janhavi S. Umak; Jitendra Sawant (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The reliability and efficiency of power distribution systems are critical for the sustained development of growing urban centers like Yavatmal, a city in Maharashtra, India. With the increasing demand for electricity driven by population growth, industrialization, and infrastructural expansion, the existing power distribution network faces significant challenges such as load imbalance, voltage instability, and high energy losses. This project proposes the design of a Load Balancing Control System (LBCS) aimed at improving the operational efficiency and stability of Yavatmal’s electrical distribution network. The system is designed to monitor real-time load data, identify overloaded feeders or substations, and dynamically redistribute electrical loads to maintain balance across the grid. The control strategy incorporates intelligent algorithms that ensure optimized power flow, reduce transmission losses, and prevent equipment overloading. Replicating the actual topology and load conditions of Yavatmal’s distribution network. Results from the simulation demonstrate that the LBCS significantly improves load uniformity, enhances voltage profiles, and minimizes outage risks. The proposed solution not only strengthens the existing infrastructure but also provides a scalable model for smart grid integration and efficient energy management in similar urban regions. analysis of a particular subject or discipline, and is often used to help the reader quickly ascertain the paper's purpose. When used, an abstract always appears at the beginning of a manuscript, acting as the point-of-entry for any given scientific paper or patent application.
Keywords: Research Paper; load balancing; electricity; distribution; yavatmal; city; problem; statements; solutions